2001
DOI: 10.1007/s002210000600
|View full text |Cite
|
Sign up to set email alerts
|

A novel postsynaptic density protein: the monocarboxylate transporter MCT2 is co-localized with δ-glutamate receptors in postsynaptic densities of parallel fiber-Purkinje cell synapses

Abstract: Confocal immunofluorescence microscopy showed strong monocarboxylate transporter 2 (MCT2) labeling of Purkinje cell bodies and punctate labeling in the molecular layer. By immunogold cytochemistry, it could be demonstrated that the MCT2 immunosignal was concentrated at postsynaptic densities of parallel fiber-Purkinje cell synapses. The distribution of MCT2 transporters within the individual postsynaptic densities mimicked that of the delta2 glutamate receptor, as shown by use of two different gold-particle si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
149
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 147 publications
(166 citation statements)
references
References 46 publications
16
149
1
Order By: Relevance
“…Commensurate with this model, monocarboxylate (including lactate) transporters have been found on neurons and astrocytes both in vitro and in vivo. Neurons primarily express the monocarboxylate transporter MCT2 (Bergersen et al, 2001;Pierre et al, 2002;Debernardi et al, 2003), the kinetics of which favor lactate uptake, whereas astrocytes express either MCT1 or MCT4 (Pierre et al, 2000;Bergersen et al, 2001;Debernardi et al, 2003), the kinetics of which favor lactate release, which is consistent with the lactate shuttle model. This lactate shuttle is stimulated during excitotoxic insults by increased concentrations of glutamate in the extracellular space.…”
Section: Introductionsupporting
confidence: 69%
“…Commensurate with this model, monocarboxylate (including lactate) transporters have been found on neurons and astrocytes both in vitro and in vivo. Neurons primarily express the monocarboxylate transporter MCT2 (Bergersen et al, 2001;Pierre et al, 2002;Debernardi et al, 2003), the kinetics of which favor lactate uptake, whereas astrocytes express either MCT1 or MCT4 (Pierre et al, 2000;Bergersen et al, 2001;Debernardi et al, 2003), the kinetics of which favor lactate release, which is consistent with the lactate shuttle model. This lactate shuttle is stimulated during excitotoxic insults by increased concentrations of glutamate in the extracellular space.…”
Section: Introductionsupporting
confidence: 69%
“…MCT3 has been localized exclusively in the retinal pigment epithelium. On the other hand, low affinity MCT4 is particularly evident in tissues with higher glycolytic rates, such as white skeletal muscle (158) and astrocytes (7,120). Its characteristics suggest an adaptation to the release of lactate in glycolytic cells.…”
Section: Monocarboxylate Transporter Membersmentioning
confidence: 99%
“…Nevertheless, in situ hybridization analyses of the mouse brain have characterized the neuronal expression of MCT2 in the cerebral cortex, hippocampus, and cerebellar cortex, including the Purkinje cell layer (81,106,154). Another immunostaining study of the rat brain for MCT2 has detected positive reactivities of neurons in the hippocampus, thalamus, olfactory bulb, and cerebellum (7,110,120). In accordance with this, an analysis of primary cultured cells gave evidence of a cellspecific localization of MCTs with an enrichment of MCT1 in astrocytes and of MCT2 in neurons (11), though another similar analysis of the rat brain has shown that all cultured cortical astrocytes express MCT2 as well as MCT1 (57).…”
Section: The Brainmentioning
confidence: 99%
See 2 more Smart Citations